AL-QUR’ĀN MESSAGE ABOUT ETHOS OF WORK IN THE PANDEMIC TIME COVID-19 - Damayanti, Eka; Firdaus; Ghany, Abdul; Hamzah, Ekawati (The Department of the Qur'anic Studies, Faculty of Ushuluddin, Adab, and Da'wah, State Institute of Islamic Studies (IAIN) Langsa, 2021)
Al-Qur’ān is the holy book as a guide for people in any condition. This including the COVID-19 pandemic that has spread across the world. This article aims to outline the message in the Qur'ān about work ethic during the Covid-19 pandemic. This article is a literature review study with the Maudhui method of the Qur'ān verses related to work ethic. It was using content analysis. The study showed that even though the pandemic is taking place, Muslims are still obliged to work because Allah expressly commands them to work. God's commandment is that humans carry out work according to their ability and earnestly for life in the world and a provision in the hereafter because work is an act of jihad fisabillah.